P5_9 Sunstorm - Beedle, Thomas James; Baldwin, Emily Jane; Cook, Naomi Esther; Evershed, Mabel Elisabeth (Physics Special Topics, 2017)
In the book “Sunstorm”, the Earth is bombarded with 7.76x10^31 J of solar energy, which in the book does not destroy the Earth as the whole human race works together to build a shield to protect the planet. However, we found that the shield as described in the book would not deflect enough energy to prevent the extinction of the human race, as the remaining 7.76x10^28 J of energy would raise the crust of the Earth to its melting point, while boiling away all of the oceans into the atmosphere. This would make it impossible for survival on the planet, meaning that contrary to the outcome of the book humanity and all other life forms on Earth would be destroyed.